Is There a Close Relationship Between The Role of Women and the Level of Poverty in Indonesia? - Faizal Amir; Hasna Shiddiqoh (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
In this era, education is a key factor that must be considered in order to break the cycle of poverty. Higher education will also encourage work to be more productive. Women are a gender that part of the workforce who need good education and health support so that their productivity increases. This study aims to determine the role of women in overcoming the national poverty rate. The data and variables used include the poverty rate, the number of female workers, the average salary of women, the number of female workers with high school education and above and the number of women who were attended by trained medical personnel during childbirth in all provinces in Indonesia in 2008-2013. As a result, the average salary of women has no significant effect on the level of poverty. Meanwhile, other independent variables based on statistics have a significant influence in reducing the national poverty rate.